Implementation of information and communication technology (ICT) for building maintenance - Ismail, Zul-Atfi (2013)
The current maintenance management method has affected the efficiency of the building facility management due to the usage of conventional method application (paper-based form and unsystematic database). Initially, the application of ICT in building maintenance contributes the new impression to the management processes in the organisation. The demands on ICT for maintenance management, hereafter denoted as Maintenance Management IT (MMIT), has shifted from being tool to automate corrective and preventive maintenance management, such as task scheduling and inventory management. The objective of this paper is to review existing literature of the technologies in maintenance management, and subsequently identify the challenge in improving the current maintenance management technologies. As a precursor to this work, the paper reviews the challenges of ICT implementation for defect diagnosis and strategic decision making in building maintenance activities. The findings reveal the need for more sophisticated maintenance management system with implementation of ICT. In conclusion, the implementation challenges of ICT for building maintenance can improve the maintenance management technologies effectiveness to provide high-quality building facility for safe and healthy environment.